2021
DOI: 10.1101/2021.05.26.443420
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic Patterns in a Complete Human Genome

Abstract: The completion of the first telomere-to-telomere human genome, T2T-CHM13, enables exploration of the full epigenome, removing limitations previously imposed by the missing reference sequence. Existing epigenetic studies omit unassembled and unmappable genomic regions (e.g. centromeres, pericentromeres, acrocentric chromosome arms, subtelomeres, segmental duplications, tandem repeats). Leveraging the new assembly, we were able to measure enrichment of epigenetic marks with short reads using k-mer assisted mappi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 96 publications
4
30
1
Order By: Relevance
“…CENP-A-directed mA was found to be higher within both large and small CDRs compared to their adjacent CpG methylated regions, consistent with short-read data for this cell line (Fig. 6d-f) (Altemose et al 2021;Gershman et al 2021). Furthermore, we found that the number of CENP-A nucleosomes detected per kilobase on single-molecule reads increased over 4-fold within ChrX CDRs compared to neighboring regions (Methods, Fig.…”
Section: Figuresupporting
confidence: 90%
See 3 more Smart Citations
“…CENP-A-directed mA was found to be higher within both large and small CDRs compared to their adjacent CpG methylated regions, consistent with short-read data for this cell line (Fig. 6d-f) (Altemose et al 2021;Gershman et al 2021). Furthermore, we found that the number of CENP-A nucleosomes detected per kilobase on single-molecule reads increased over 4-fold within ChrX CDRs compared to neighboring regions (Methods, Fig.…”
Section: Figuresupporting
confidence: 90%
“…To test DiMeLo-seq's ability to measure protein occupancy in heterochromatic, repetitive regions of the genome we targeted H3K9me3, which is abundant in pericentric heterochromatin. We chose to target H3K9me3 in HG002 cells because the chromosome X centromere has been completely assembled for this male-derived lymphoblast line (Nurk et al 2021), and many different sequencing data types are available for it (Gershman et al 2021). To validate the specificity of targeted methylation, we calculated the fraction of adenines methylated within HG002 CUT&RUN H3K9me3 peaks (Altemose et al 2021) compared to the fraction of adenines methylated outside of broadly defined peaks (Methods).…”
Section: Mapping Histone Modifications In Heterochromatin With Dimelo-seqmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome assembly is a foundational practice of quantitative biological research with increasing utility. By representing the genomic sequence of a sample of interest, genome assemblies enable researchers to annotate important features, quantify functional data, and discover/genotype genetic variants in a population [1][2][3][4][5][6] . Modern draft eukaryotic genome assembly graphs are typically built from a subset of four Whole Genome Shotgun (WGS) sequencing data types: Illumina short reads 7,8 , Oxford Nanopore Technologies (ONT) long reads 9 , PacBio Continuous Long Reads (CLR), and PacBio High-Fidelity (HiFi) long reads 9,10 , all of which have been extensively described [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%